2018
DOI: 10.1111/dth.12802
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV inhibits cell proliferation in vulvar squamous cell carcinoma through the TGF‐β/Smad signaling pathway

Abstract: Objective To explore the inhibition of the proliferation of vulvar squamous cell carcinoma (VSCC) by astragaloside IV. Methods MTT examined the cell proliferation of VSCC. Flow cytometry analyzed cell cycle and apoptosis. Western blot assay detected the expression of some relevant proteins. Results AS‐IV reduced the proliferation of SW962 cells in a concentration‐ and time‐dependent manner, induced cell‐cycle arresting in G0/G1 phase, as demonstrated by the up‐regulation of P53 and P21 expression, and the down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Accordingly, the combination of vanadium and the traditional chemotherapy drug carboplatin induces a more potent G0/G1 cell cycle arrest [ 167 ]. Similarly, astragaloside IV also achieves cancer treatment via TGF-β-induced cell cycle arrest in the G0/G1 phase in vulvar squamous cell carcinoma, which enhanced cancer cell apoptosis simultaneously by increasing the expression of apoptotic genes including cleaved caspase-3 [ 168 ]. Meanwhile, heteronemin, a natural compound extracted from marine sponges, can reduce the expression of TGF-β1 and intercellular adhesion molecule 1, and inhibits cancer cell adhesion, motility, and proliferation in the bile duct cancer, cholangiocarcinoma [ 169 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Accordingly, the combination of vanadium and the traditional chemotherapy drug carboplatin induces a more potent G0/G1 cell cycle arrest [ 167 ]. Similarly, astragaloside IV also achieves cancer treatment via TGF-β-induced cell cycle arrest in the G0/G1 phase in vulvar squamous cell carcinoma, which enhanced cancer cell apoptosis simultaneously by increasing the expression of apoptotic genes including cleaved caspase-3 [ 168 ]. Meanwhile, heteronemin, a natural compound extracted from marine sponges, can reduce the expression of TGF-β1 and intercellular adhesion molecule 1, and inhibits cancer cell adhesion, motility, and proliferation in the bile duct cancer, cholangiocarcinoma [ 169 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…To explore the potential mechanism of BZW1, TGF-β1/Smad pathway was investigated. It is well known that TGFβ/Smad pathway is involved in cell proliferation [19][20][21]. Results shown that BZW1 over-expression activated the TGF-β1/Smad pathway.…”
Section: Discussionmentioning
confidence: 90%
“…SMAd and downstream TGF-β intracellular signaling transfer the ligand-receptor interaction signal from the cytoplasm to the nucleus. In a previous study, in VScc cells, AS-IV was shown to improve the dysfunctions of the TGF-β/SMAd pathway, determined based on the elevated TGF-βRII and Smad4 levels; it was also found that AS-IV induced autophagy in SW962 cells, and markedly increased Beclin-1 and Lc3-II levels, and decreased p62 protein levels (19).…”
Section: Promotion Of Autophagymentioning
confidence: 89%
“…However, Bcl-2 can inhibit the release of cyt c and avoid the intrinsic apoptosis induced by Bax (15). Research has indicated that AS-IV can enhance the Bax/Bcl-2 ratio to induce intrinsic apoptosis in a number of types of cancer, including colorectal cancer (cRc), breast cancer, lung cancer, vulvar squamous cell cancer (VScc) and hepatocellular carcinoma (Hcc) (16)(17)(18)(19)(20)(21).…”
Section: Effects Of As-iv In Cancer Modelsmentioning
confidence: 99%